Tire–pavement tractive rolling contact under turning conditions: towards pavement top-down cracking. Issue 3 (23rd February 2022) - Manyo, E. Y.; Reynaud, P.; Picoux, B.; Tautou, R.; Allou, F.; Petit, C.; Nélias, D.
ABSTRACT: This paper describes the elastic tire–pavement tractive rolling contact, by means of a semi-analytical method, in order to analyse top-down cracking. The model includes the actual tire profile and assumes the tyre to be elastic, linear and homogeneous, as modelled by an equivalent Young's modulus. The pavement is modelled as a half-space layer composed of asphalt concrete acting as a homogeneous elastic material. Results display the vertical contact stress and shear contact stress in both braking and turning cases; they also highlight the stick/slip zones within the contact area. When applied, these stresses allow computing the tensile strain responses at the pavement surface. Analysis shows that the maximum tensile strains are able to cause top-down cracking. Such strains are higher than the level considered in current pavement design models. A top-down cracking analysis is ultimately conducted according to the French method of bottom-up pavement design.